2011
DOI: 10.1111/j.1365-2958.2011.07743.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA‐binding sequences for CcaR in the cephamycin–clavulanic acid supercluster of Streptomyces clavuligerus

Abstract: SummaryRT-PCR analysis of the genes in the clavulanic acid cluster revealed three transcriptional polycistronic units that comprised the ceaS2-bls2-pah2-cas2, cyp-fd-orf12-orf13 and oppA2-orf16 genes, whereas oat2, car, oppA1, claR, orf14, gcaS and pbpA were expressed as monocistronic transcripts. Quantitative RT-PCR of Streptomyces clavuligerus ATCC 27064 and the mutant S. clavuligerus ccaR::aph showed that, in the mutant, there was a 1000-to 10 000-fold lower transcript level for the ceaS2 to cas2 polycistro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 39 publications
2
59
0
2
Order By: Relevance
“…asoensis (222), cmcI and ceaS2-II in S. clavuligerus (223), and fdmR2 in S. griseus (219). Degeneracy of the repeats may make the structure of the targets difficult to characterize, perhaps explaining why the spacers appear to vary from 4 to 15 nt in different targets (216,217,219). Alternatively, these differences could perhaps be related to variations in the structure of SARPs.…”
Section: A Survey Of Sarpsmentioning
confidence: 99%
See 2 more Smart Citations
“…asoensis (222), cmcI and ceaS2-II in S. clavuligerus (223), and fdmR2 in S. griseus (219). Degeneracy of the repeats may make the structure of the targets difficult to characterize, perhaps explaining why the spacers appear to vary from 4 to 15 nt in different targets (216,217,219). Alternatively, these differences could perhaps be related to variations in the structure of SARPs.…”
Section: A Survey Of Sarpsmentioning
confidence: 99%
“…The specific sequences recognized by SARPs generally overlap the Ϫ35 regions of their targets, but sometimes the sequences are far from the transcriptional start point (tsp) of their target genes. Some SARP-binding sites contain three discernible heptamers, such as those upstream of actII-ORF1 and actVI-ORF1 in S. coelicolor (29), claR, cefD, and cefF in S. clavuligerus (216), vlmJ and vlmA-vlmH in Streptomyces viridifaciens (217), dnrD in S. peucetius (218), fdmD in S. griseus (219), pimM in S. natalensis (220), and so on. Other sites contain only two obvious heptamers, such as sanO-sanN in S. ansochromogenes (221), polB and polC in Streptomyces cacaoi subsp.…”
Section: A Survey Of Sarpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CcaR binding to the promoter of ceaS2 positively affected cas2 expression (Santamarta et al, 2011;Paradkar, 2013). Medema et al (2011a) conducted a genome-wide gene expression analysis of a randomly mutated industrial strain of S. clavuligerus compared to the wild type and showed that the expression of cas2, claR, and ccaR increased by 5.47-fold, 2.23-fold, and 5.6-fold, respectively, in the industrial one.…”
Section: Discussionmentioning
confidence: 99%
“…Both the CA supercluster and the clavam cluster lie on the chromosome, whereas the paralog cluster is located on the pSCL4 plasmid (37). The complexity of CA-clavam biosynthesis is also reflected at the level of regulation, and at least 6 regulatory genes (ccaR [45,52], claR [43], cvm7P [59], and orf21 to orf23 [25,55]) were identified among the three gene clusters. Intricate cross-regulation between the arginine and CA (12, 51), cephamycin C and CA (44,45), and CA and holomycin (11) pathways were also reported.…”
mentioning
confidence: 99%